Big Nate : payback time! - Peirce, Lincoln (Big Nate, 2019)
Nate faces his own unique struggles in sixth grade which include developing an allergy to Mrs. Godfrey and landing himself in detention. But a showdown on the soccer field after school could be the thing that finally does him in.